Pengaruh Pemahaman Perpajakan, Pemeriksaan Perpajakan Yang Dimoderasi Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Pada Perkumpulan Konsultan Praktisi Perpajakan Indonesia (PERKOPPI) - Diah Ayu Putri Rokhanah; Gilbert Rely; Bambang Prayogo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The research aims to determine whether there is an influence of tax understanding, and tax audits moderated by tax sanctions on taxpayer compliance at the Indonesian Tax Practitioners Consultants Association (PERKOPPI). The sample selection in this study used the question method with predetermined criteria with a total sample of 100 respondents. The type of data used is primary data. The design used in this study is hypothesis testing using IBM SPSS Statistics version 22. The results of this study conclude that (1) Tax understanding has a positive and significant effect on taxpayer compliance (2) Tax audit has a positive and significant effect on taxpayer compliance (3 ) Understanding of Taxes, Simultaneous (together) tax audits have a significant effect on taxpayer compliance. (4) Tax Sanctions strengthen the influence of tax understanding on taxpayer compliance (5) Tax Sanctions strengthen the effect of tax audits on taxpayer compliance.